Daun Sirih Merah Sebagai Perawatan Tradisional Dalam Penyembuhan Luka Perineum - Reza Bintangdari Johan; Nur Indah Noviyanti; Kustiningsih Kustiningsih; Gusriani Gusriani (JURNAL KESEHATAN DELIMA PELAMONIA, 2023)
Perineal tears can occur during labor. This tear causes an injury. This situation can be an entry point for microorganisms that can cause infection if not treated properly. The wound-healing process varies from person to person. However, there are several ways to treat perineal wounds are traditional and non-traditional. This study aimed to determine the perineal wound healing period with red betel leaves. Quasi-experimental research with a posttest-only design approach with non-equivalent groups. In this study, 22 postpartum mothers, the experimental group using red betel leaves, and the control group using clean-dry dressing treatment, which would assess the wound healing process with the REEDA scale. The sampling technique uses accidental sampling. The data analysis used is an independent-Sample T-test. The results, perineal wounds using red betel leaves (5.45 days) were two days faster than dry clean treatment (7.55 days). The REEDA sign was no longer visible in the red betel leaf group on the eighth day. It was still possible to see the control group on the ninth day. Moreover, proper wound care, a healthy diet, and good hygiene contribute to wound healing. Mothers should be confident in their abilities and think positively.